Blink : the power of thinking without thinking - Gladwell, Malcolm, 1963- (New York : Little, Brown and Co., 2005)
Presents a study of how people think without thinking, looking at the brain processes involved in making snap decisions, discussing why some people seem to have great instincts while others consistently choose unwisely, and examining ways to control the process.
The statue that didn't look right -- The theory of thin-slicing -- The locked door -- The Warren Harding error -- Paul Van Riper's big victory : creating structure for spontaneity -- Kenna's dilemma : the right-and wrong-way to ask people what they want -- Seven seconds in the Bronx : the delicate art of mind-reading -- Conclusion: listening with your eyes : the lessons of blink.
Includes bibliographical references and index.
Booklist
Library Journal Starred
Pub Weekly
Adult.
Adult
Keywords: Decision making; Intuition; Decision making; Intuition